COMPARISON WITH INTENSITY OF SECONDARY DENGUE INFECTION BY DETECTING DENGUE-SPECIFIC IMMUNOGLOBULIN G ANTIBODIES - Poddar, Sudipta; Hati, Amiya Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Detection of dengue-specific immunoglobulin G (IgG) antibodies in the serum of healthy individuals signifies previous dengue infection. This phenomenon can be utilized to demonstrate dengue activity in a suspected area and to stratify intensity of infection in the urban and rural surroundings. Methods: Serum samples of altogether 881 healthy volunteers, 560 persons living in the central part of the city Kolkata and 321 individuals residing at a village Memari (highly endemic for dengue), 85 Km away from Kolkata, having no apparent proof of dengue activity were examined for the detection of dengue-specific IgG antibodies. Results: Of 560 serum samples collected from Kolkata, 55.5% (249) were IgG reactive. Respective figures for Memari were 321 and 25.3% (81). This indicated that the virus was also active at rural area, though the endemic property was lower than in Kolkata. In both urban (r=âˆ’0.585, p=0.017) and rural (r=âˆ’0.392, p=0.013) West Bengal, the suspected and IgG reactive cases apparently negatively correlated with age, but the percentage of reactivity was found to increase with age. The number of IgG reactive cases was significantly more in Kolkata than at Memari, indicating that dengue virus was active at Memari though the endemic property was much lower than that of Kolkata and chances of secondary dengue infection vis-a-vis dengue hemorrhagic fever would be more in Kolkata than at Memari. Conclusion: Evaluation of IgG specific dengue antibodies can be utilized to compare intensity of secondary dengue infection vis-a-vis DHF and its endemic property in different places, furnish a preliminary idea.